2010
DOI: 10.1007/s13312-010-0121-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin induced vitamin d deficiency presenting as proximal muscle weakness

Abstract: A 6-year-old girl presented with proximal muscle weakness of lower limbs. She was receiving phenytoin for epilepsy for 2 years. Serum phenytoin level was within therapeutic range. Serum 25(OH) vitamin D was low (5 ng/mL) and serum parathyroid hormone level was high. After administration of oral vitamin D, muscle weakness improved and vitamin D level increased to 39.11 ng/mL. Proximal muscle weakness due to vitamin D deficiency following phenytoin intake is rare in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We have no significant number of students taking vitamin D-influencing medication such as anti-seizure drugs [42][43][44], steroid drugs [45][46][47][48][49][50][51], fat absorption reduction [45,[52][53][54], cholesterol metabolism modification [45,[55][56][57] or diuretics. The only anti-inflammatories drug [45][46][47][48][49][50][51], reported is "Ibuprofen 200mg" (n = 120), which does not affect the vitamin D level.…”
Section: Diseases and Medicine Usagementioning
confidence: 99%
“…We have no significant number of students taking vitamin D-influencing medication such as anti-seizure drugs [42][43][44], steroid drugs [45][46][47][48][49][50][51], fat absorption reduction [45,[52][53][54], cholesterol metabolism modification [45,[55][56][57] or diuretics. The only anti-inflammatories drug [45][46][47][48][49][50][51], reported is "Ibuprofen 200mg" (n = 120), which does not affect the vitamin D level.…”
Section: Diseases and Medicine Usagementioning
confidence: 99%
“…2,[8][9][10][11][12][13] In more recent years, these proposed mechanisms and subsequent studies have raised similar concerns regarding the impact of some of the new, nonenzyme-inducing AEDs on bone health as well. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15] In the pediatric population, one study has shown that serum markers of bone health, including 25-hydroxy vitamin D (25(OH)D) levels, differ significantly between pediatric patients with epilepsy and controls. 7 Serum markers of bone turnover are also elevated in patients treated with AEDs, potentially implying risk for future bone loss.…”
Section: Introductionmentioning
confidence: 99%